Leadership for Youth Empowerment Within a Family-Based Community Program. Issue 6 (November 2019) - Gil, Elizabeth
This article examines the perceptions of students who observed their adult family members' participation and also participated in Connection and Access through Technology (CAtT), a family-oriented community-based program that taught technology skills to adult family members of school-aged children. This qualitative study applies conceptions of empowerment, for youth and community settings, to understand how program structures promoted immigrant Latino family members' empowerment. In CAtT, parents gained technology skills, which they applied to their daily lives and to their children's schooling, and developed leadership skills. Students experienced a sense of belonging, agency, competence, and leadership through increasing technology skills and having opportunities to contribute to the program, including through teaching others. Witnessing positive experiences of adult family members in the program also represented possibilities for children's personal successes. Findings suggest that leaders' ability to recognize and employ nontraditional parental involvement that builds on families' cultural characteristics results in fostering student empowerment. Exposure to programs such as CAtT, which empower Latino immigrant families and which have the potential to alter traditional structures, is essential in the development of leaders for social justice and culturally responsive leadership.